Experience of a New Dedicated Meta-analysis Tool in Systematic Review and Meta-Analysis on Training Performances of Virtual Reality Bronchoscopy Simulation (Journal of Informatics and Mathematical Sciences, 2018)
The increasing employment of virtual reality bronchoscopy simulation makes it essential to validate the effectiveness of training. This systematic review and meta-analysis performs comparisons among trained groups. Well-known sources (i.e., PubMed, Scopus, and Google Scholar) were systematically searched using a Boolean query based on PRISMA guidelines. The inclusion criteria were peer-reviewed English articles considering virtual reality training simulation based on flexible bronchoscopy for novices and experts, and the studies without enough data or not relevant in content were excluded. Then, the meta-analysis procedure based on random-effects model, heterogeneity and publication bias tests, and subgroup analyses were performed. Eight studies comprising two randomized clinical trials, two prospective, and four observational studies were analyzed. The results for forest plots were illustrated and the significant p values of the target groups were indicative of the fact that the virtual reality bronchoscopy simulation was effective between the groups. The outcomes of meta-regression analyses for sample size and published year showed that the latter one can explain most of the heterogeneity between the studies. And, the funnel plots were indicative of no publication bias. Finally, the high rates of explained variance between studies achieved by subgroup analyses were 89% and 52%. The virtual reality bronchoscopy simulation for training the target groups will be beneficial for both novice trainees and experts. The outcomes of current study showed the effectiveness of virtual reality training technique along with the consistent results in terms of meta-analysis, publication bias, meta-regression, heterogeneity, and subgroup analysis. The stand-alone meta-mums tool is available by requesting through the corresponding authors' email addresses.
Keywords: Virtual reality; Bronchoscopy; Training; Meta-analysis; Novices; Experts